Persepsi Siswa Tentang Lingkungan Sekolah Terhadap Motivasi Belajar Mereka Pada Mata Pelajaran IPS di SMP Negeri 5 Rantau - Natalia, Dessy (Yayasan Sembilan Pemuda Indonesia, 2024)
The school environment is very important for students, especially in terms of the learning process. Therefore, the school environment greatly influences the student learning process. Students must be highly motivated to achieve learning goals. There are two motivations, namely intrinsic and extrinsic. Both of these motivations are influenced by the school environment. This research involved 122 students in grades 7, 8 and 9 at SMP Negeri 5 Rantau Bayur. Proportional random sampling was used to take samples from 61 students out of 122 students. The school environment was the independent variable, and learning motivation was the dependent variable. To collect data, observation, questionnaires, and documentation were used. Regression analysis and descriptive percentages were used to analyze the data. The results of descriptive analysis of data regarding the influence of the school environment for 61 students showed that 14 students were very high (19.44%), 46 students were high (79.17%), and 1 student was low (1.39%). Of the 61 samples, student learning motivation showed 7 students were very high (9,72%), 50 students were high (84.72%), and 4 students were low (5.56%). There is a significant influence between the school environment on learning motivation, and the relationship between the two variables is linear.